1992
DOI: 10.1111/j.1398-9995.1992.tb02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold urticaria as a model of mediator release: platelet factor 4, eosinophil cationic protein and histamine

Abstract: Platelet factor 4 (PF4) has previously been linked to precipitation of cold urticaria (CU). The aim of the study was to assess the liberation of PF4, eosinophil cationic protein (ECP) and histamine after cold challenge in patients with CU. Ten controls and 8 patients with CU verified by clinical data and cold challenge test were investigated. Assessment of histamine, ECP and PF4 were done using radioimmunoassays. In patients histamine increased after 10 min on the challenged arm (NS), PF4 increase was statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
2
0
3
Order By: Relevance
“…Early studies had suggested blood platelet activation in physical urticaria on the basis of the finding of enhanced plasma level of PF‐4 after cold stimulus (14). In contrast to these results, Rosenkranz et al (18) did not observe any difference concerning PF‐4 release between patients and controls after cold challenge test, suggesting that platelets are not directly involved in cold urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies had suggested blood platelet activation in physical urticaria on the basis of the finding of enhanced plasma level of PF‐4 after cold stimulus (14). In contrast to these results, Rosenkranz et al (18) did not observe any difference concerning PF‐4 release between patients and controls after cold challenge test, suggesting that platelets are not directly involved in cold urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with a small sample size evaluated the role of platelet activation in cold urticaria and provided controversial results [89,90,91]. A significant increase in soluble P-selectin was seen in patients with dermatographic urticaria when compared to healthy controls and rhinitis subjects [75].…”
Section: Platelets In Chronic Inducible Urticariamentioning
confidence: 99%
“…Debido a que los anti-anticuerpos están dirigidos contra la IgE y su receptor de alta afinidad (FceR1) que se encuentra principalmente en los mastocitos y los basófilos, es de esperar que estas células tengan un papel importante, principalmente los mastocitos, debido a que son los que se encuentran en mayor cantidad en el organismo y, en especial, en la piel. Los trabajos utilizando retos in vivo han demostrado el incremento de varios mediadores luego del reto con frío, tales como la histamina, la prostaglandina D2, el factor activador de plaquetas y los factor quimioatrayentes de neutrófilos y eosinófilos (41)(42)(43).…”
Section: Urticaria Con Respuesta Atípicaunclassified